Does the socioeconomic status predict health service utilization in persons with enhanced health care needs? Results from a population-based survey in persons with spinal cord lesions from Switzerland - Christine Fekete; Caroline Debnar; Anke Scheel-Sailer; Armin Gemperli (BMC, 2022)
Abstract Background Evidence suggests that the socioeconomic status (SES) affects individuals' health service utilization. Spinal cord injury is a condition that often leads to physical impairments and enhanced health care needs. It therefore presents an informative and yet under-researched case in point to investigate social inequalities in health service utilization. This study aims to describe associations between SES and health service utilization in adults with spinal cord injury from Switzerland. Methods We use cross-sectional data from 1,294 participants of the Swiss Spinal Cord Injury Cohort Study community survey 2017. SES was operationalized with education, household income, perceived financial hardship, subjective status, and granting of supplementary financial benefits. Health service utilization was assessed with information on visits to 13 different health care providers and four health care institutions (inpatient stays, outpatient clinics, emergency departments, specialized spinal cord centers) during the past 12 months. The dichotomized outcomes on service utilization (visited vs. not visited) were regressed on SES indicators, including adjustments for sociodemographics, lesion characteristics, and health status. Results Persons with higher SES reported higher likelihood for specialist, dentist, and dental hygienist visits and reported utilizing a larger number of different care providers. Further, specific SES indicators were associated with certain care provider visits (i.e., higher education and subjective status: higher odds for pharmacist visits; higher income: higher odds for natural healer visits; higher subjective status: higher odds for chiropractor visits; supplementary benefit granting: higher odds for general practitioner and home care service visits). We found statistically non-significant trends towards lower likelihood for inpatient stays, outpatient clinic and emergency department visits and enhanced likelihood for specialized spinal cord-center visits in higher SES groups. Conclusions This study generally supports the claim that basic health care provision is guaranteed for all patients with spinal cord injury in Switzerland, independently of their SES. However, social inequalities were still observed for the utilization of specific providers, such as oral health care providers. Given that oral health is key for health maintenance in persons with spinal cord injury, specific interventions to enhance regular dental check-ups in lower SES groups are highly recommended.